Erfolgreiche deutsche Kabeljaumarkierungen bei Grönland - Institut für Seefischerei, Hamburg (1961)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010